2020
DOI: 10.3390/ma13051245
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Oil Palm Empty Fruit Bunch Resources in Nanocellulose Hydrogel Production for Versatile Applications: A Review

Abstract: Oil palm empty fruit bunch (OPEFB) is considered the cheapest natural fiber with good properties and exists abundantly in Malaysia. It has great potential as an alternative main raw material to substitute woody plants. On the other hand, the well-known polymeric hydrogel has gathered a lot of interest due to its three-dimensional (3D) cross-linked network with high porosity. However, some issues regarding its performance like poor interfacial connectivity and mechanical strength have been raised, hence nanocel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 130 publications
(143 reference statements)
1
47
0
Order By: Relevance
“…In addition, oil palm EFB has gained interest in the polymeric hydrogel because of its benefit as a three-dimensional (3D) cross-linked feature with high porosity. Nanocellulose EFB fibre has also been introduced in the 3D printing technique in recent hydrogel production since it contained high complexity and mechanical strength (Padzil et al, 2020). The 3D printing technique could enhance the hydrogel properties which can also be carried out in bulk amount in single processing.…”
Section: Advanced Application For Pulp and Paper Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, oil palm EFB has gained interest in the polymeric hydrogel because of its benefit as a three-dimensional (3D) cross-linked feature with high porosity. Nanocellulose EFB fibre has also been introduced in the 3D printing technique in recent hydrogel production since it contained high complexity and mechanical strength (Padzil et al, 2020). The 3D printing technique could enhance the hydrogel properties which can also be carried out in bulk amount in single processing.…”
Section: Advanced Application For Pulp and Paper Technologymentioning
confidence: 99%
“…The oil palm waste is proving to be an effective alternative to reduce production costs in the palm oil industry by maximizing the usage through by-products. The palm oil industry was identified as biomass largest producer, generated nearly 23 million tonnes residues with around 90 % came from plantations whereas the remaining 10 % of oil extraction came from the mills (Padzil et al, 2020). The largest oil palm producer was Malaysia before Indonesia seized the title in 2005 (MPOB, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malaysia is the second-largest palm oil producer and exporter country. It is being reported that the palm oil industries in Malaysia are generating over 40 million tonnes of oil palm biomass, including about 23 million tons of oil palm empty fruits bunches [ 28 , 29 ]. The high cellulose content of OPEFB (≥44%) and its huge generation make the OPEFB ideal for producing CNF to use as a bio-sorbent [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is being reported that the palm oil industries in Malaysia are generating over 40 million tonnes of oil palm biomass, including about 23 million tons of oil palm empty fruits bunches [ 28 , 29 ]. The high cellulose content of OPEFB (≥44%) and its huge generation make the OPEFB ideal for producing CNF to use as a bio-sorbent [ 29 ]. Over the years, various methods have been implemented to isolate the cellulose from various lignocellulosic biomasses, including chemical process, mechanical process, and chemo-mechanical process [ 27 , 28 , 30 ].…”
Section: Introductionmentioning
confidence: 99%